Successful viral adaptation of Classical Swine Fever (strain C) to cell culture in order to produce vaccines - Paneque Zayas, Mayelin; del Toro Yen, del Toro Yen; Domínguez Odio, Aníbal (Spei Domus, 2019)
Introduction: Classical swine fever (CSF) is a viral, infectious and cross border disease that causes important economic losses worldwide. Systematic and preventive immunization with live attenuated vaccines is pretty useful for its control; among these lapinized vaccines are within the most used. However, ethical limitations surrounding its production obliges bio-pharmaceutical industry to search for alternatives. The aim of this research is to adapt strain C of the CSF virus to a rabbit and pig cell culture. Methodology: rabbit kidney lines (RK-13) and pig’s (PK-15) were used. Both were infected with an homogenous spleen + blood, retrieved from white neo-Zealand rabbits, inoculated with master seed virus (strain C, 4th pass) from lapinized vaccine against the PPC fabricated by LABIOFAM, Cuba. In order to evaluate viral adaptation and replication within cellular lines, during the 23rd passes post-infection, it was identified a fragment of gen that codifies the E2 protein from the CSF virus, through reverse transcription technique –Polymerase chain reaction (RT-PCR) and the quantification of infectious viral titles (DICT50 /mL) by immunoperoxidase. Results: lapinidized strain C was adapted to cellular lines RK-13 and PK-15 after 23 successive passes, obtaining in the last one greater levels of viral replication with infectious titles of 105.8 DICT50 /mL. Conclusions: cellular lines RK-13 and PK-15 were susceptible to strain C infection, although PK-15 showed greater levels of viral replication.